2020
DOI: 10.1055/a-1027-6921
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic radial incision and cutting for Crohn’s Disease-associated intestinal stricture: a pilot study

Abstract: Background and study aims Intestinal stricture associated with Crohn’s disease (CD) is usually treated by endoscopic balloon dilation (EBD) or stricture plasty. Although EBD is effective and safe for such strictures, refractory stricture after EBD poses a problem. Hence, other novel approaches for these refractory strictures are required. On the other hand, the efficacy of radial incision and cutting (RIC) method for esophageal stricture after esophagogastric surgery is reported. In this pilot study, we adopte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…Although intestinal stenosis has diverse causes, a recent study showed that RIC can be used to treat any type of stenosis (primary or secondary) less than 2 cm in length. 18 We successfully conducted RIC in a patient with CMUSE and intestinal stenosis using SBE, and no adverse events occurred. The patient was asymptomatic during the 3-month follow-up.…”
Section: Retrieval Of Retained Capsule Endoscopy By Device-assisted Ementioning
confidence: 85%
See 2 more Smart Citations
“…Although intestinal stenosis has diverse causes, a recent study showed that RIC can be used to treat any type of stenosis (primary or secondary) less than 2 cm in length. 18 We successfully conducted RIC in a patient with CMUSE and intestinal stenosis using SBE, and no adverse events occurred. The patient was asymptomatic during the 3-month follow-up.…”
Section: Retrieval Of Retained Capsule Endoscopy By Device-assisted Ementioning
confidence: 85%
“…3 RIC is effective for treating refractory benign esophageal strictures, benign anastomotic stenoses, and CD-associated intestinal strictures. [18][19][20][21] At present, the indications of RIC are not clear.…”
Section: Retrieval Of Retained Capsule Endoscopy By Device-assisted Ementioning
confidence: 99%
See 1 more Smart Citation
“…However, IT knife stricturoplasty to treat refractory fibrostenotic strictures has been described only in a few case reports. 4 6 We present a patient with Crohn's disease whose abdominal pain resolved after IT knife stricturoplasty of colorectal strictures and fecalith decompaction of a diverticulum.…”
Section: Case Reportmentioning
confidence: 99%
“…We previously reported the e cacy of radial incision and cutting (RIC) method for intestinal strictures in ve patients with Crohn's disease (CD) as a pilot study [14]. RIC was initially reported as a dilation technique for refractory stenoses that developed after surgical resection of esophagogastric diseases.…”
Section: Introductionmentioning
confidence: 99%